A novel Pd decorated polydopamine-SiO2/PVA electrospun nanofiber membrane for highly efficient degradation of organic dyes and removal of organic chemicals and oils. (1st December 2020) - Yin, Hao; Zhao, Jie; Li, Yuqi; Huang, Liulian; Zhang, Hui; Chen, Lihui
Abstract: A multifunctional and flexible Pd decorated Polydopamine-SiO2 /PVA electrospun nanofiber membrane was developed by a facile, green, one-step reduction and fixation strategy for simultaneously removal of multiple pollutants from water. Pd NPs were reduced in a mild and green environment with the deposition of dopamine, avoiding secondary pollution of water. The in situ reduced Pd NPs were evenly distributed and firmly immobilized on the nanofiber membrane, effectively avoids the aggregation, thereby greatly improving the catalytic activity. After a single filtration, the developed membrane can simultaneously remove oils, organic chemicals and dyes from water with a high flux (up to 8000 L m −2 ·h −1 ). The removal efficiency for organic chemicals and oils can reach to 99.9% and the degradation efficiency for dyes (e.g., MB and CR) are also very high, up to 99%. More interestingly, the membrane showed robust mechanical properties and corrosion resistance, that can be used in acidic, alkaline, salty and even hot water environment. Besides, the membrane can be reused for at least 10 separation cycles without a significant reduction in separation efficiency, demonstrating excellent reusability and stability.